Neurogenesis in the human hippocampus and its relevance to temporal lobe epilepsies - Siebzehnrubl, Florian A.; Blumcke, Ingmar (Epilepsia (Copenhagen), 2008)
Summary Ample evidence points to the dentate gyrus as anatomical region for persistent neurogenesis in the adult mammalian brain. This has been confirmed in a variety of animal models under physiological as well as pathophysiological conditions. Notwithstanding, similar experiments are difficult to perform in humans. Postmortem studies demonstrated persisting neurogenesis in the elderly human brain. In addition, neural precursor cells can be isolated from surgical specimens obtained from patients with intractable temporal lobe epilepsy (TLE) and propagated or differentiated into neuronal and glial lineages. It remains a controversial issue, whether epileptic seizures have an effect on or even increase hippocampal neurogenesis in humans. Recent data support the notion that seizures induce neurogenesis in young patients, whereas the capacity of neuronal recruitment and proliferation decreases with age. Animal models of TLE further indicate that these newly generated neurons integrate into epileptogenic networks and contribute to increased seizure susceptibility. However, pathomorphological disturbances within the epileptic hippocampus, such as granule cell dispersion (GCD), may not directly result from compromised neurogenesis. Still, the majority of adult TLE patients present with significant dentate granule cell loss at an end stage of the disease, which relates to severe memory and learning disabilities. In conclusion, surgical specimens obtained from TLE patients represent an important tool to study mechanisms of stem cell recruitment, proliferation and differentiation in the human brain. In addition, increasing availability of surgical specimens opens new avenues to systematically explore disease pathomechanisms in chronic epilepsies.